Farmers' prioritization of climate-smart agriculture (CSA) technologies - Khatri-Chhetri, Arun; Aggarwal, Pramod K.; Joshi, Pramod K.; Vyas, S. (Elsevier, 2017)
Addressing climate change impacts on agriculture is special challenge. There are number of factors that influence the extent to which farmers in a particular location adopt CSA technologies. This study applied a participatory assessment method to assess farmers' preferences and willingness-to-pay for selected CSA practices and technologies in diverse rainfall zones. The study found that farmers' preferences for CSA technologies are marked by some commonalities as well as differences according to their socio-economic characteristics and rainfall zones. The most preferred technologies by local farmers were crop insurance, weather-based crop agro-advisories, rainwater harvesting, site-specific integrated nutrient management, contingent crop planning and laser land levelling. The results also indicate that farmers' preferences and willingness-to-pay are influenced by technologies and their cost of implementation. This study shows the potential for using a participatory CSA prioritization approach to provide information on climate change adaptation planning at local level.